Mathematical and experimental investigation of water migration in plant xylem - Hong, Jiaju; Liu, Sheng; Glover, Paul; Wu, Shenyi; Yan, Yuying (Elsevier, 2017)
Plant can take water from soil up to several metres high. However, the mechanism of how water rises against gravity is still controversially discussed despite a few mechanisms have been proposed. Also, there still lacks of a critical transportation model because of the diversity and complex xylem structure of plants. This paper mainly focuses on the water transport process within xylem and a mathematical model is presented. With a simplified micro channel from xylem structure and the calculation using the model of water migration in xylem, this paper identified the relationship between various forces and water migration velocity. The velocity of water migration within the plant stem is considered as detail as possible using all major forces involved, and a full mathematical model is proposed to calculate and predict the velocity of water migration in plants. Using details of a specific plant, the velocity of water migration in the plant can be calculated, and then compared to the experimental result from Magnetic Resonance Imaging (MRI). The two results match perfectly to each other, indicating the accuracy of the mathematical model, thus the mathematical model should have brighter future in further applications.